DESIGN AND BUILD INVENTORY MANAGEMENT INFORMATION SYSTEM USING THE SCRUM METHOD - Ashari, Ilham Firman; Aryani, Annisa Jufe; Ardhi, Alief Moehamad (Jurnal Sistem Informasi, 2022)
PT Telkom Akses (PTTA) is a subsidiary of PT Telekomunikasi Indonesia, Tbk (Telkom) which share owned entirely by Telkom. PT Telkom Akses is engaged in the business of providing construction services and network infrastructure management. Data collection manually can result in slow data management and will have an impact on the workflow of PT. Telkom Akses 3 Ilir Palembang. There will be a lot of damaged or duplicated data and finding data will be difficult. Therefore, it is necessary to develop a system that can collect data on incoming and outgoing goods, namely a Web-based Inventory System. The development of this inventory system uses the CodeIgniter3 Framework and Scrum methodology. Scrum is one of the methods that uses the Agile principal, which refers to team collaboration, product incremental, and iterative processes to achieve goals. The results of the evaluation of system testing using the black-box testing method show that the developed system can run well and as expected. Hopefully with the present of this system, it can help PT Telkom Akses 3 Ilir Palembang in performing incoming and outgoing goods data collection. Keyword: Inventroy System, Web, Codeigniter 3, Scrum, BlackBox Testing